"They would make you feel stupid" - Ability grouping, Children's friendships and psychosocial Wellbeing in Irish primary school. (October 2021) - McGillicuddy, Deirdre
Abstract: Increasing international attention on wellbeing places the onus on education systems to support children's positive psychosocial development. Despite broad and rich literature highlighting the limitations of implementing ability grouping as pedagogy and its impact on how children 'do' and 'feel' learning in school, this practice still persists in systems across the OECD. This Irish study draws on qualitative and sociometric data from 3 case study schools with 100 children. It explores how teachers cast an 'invisible hand' over children's peer networks, shaping friendships and patterns of inclusion/exclusion within the classroom. It builds on current literature in the field exploring how peer interaction is influenced by ability group assignment using network analysis. Findings also reveal the psychosocial impact of these dynamics, with children assigned to lower ability groups most impacted by lower social status, exclusion from peers and increased experience of bullying. These experiences evoked feelings of disengagement, anger and isolation. Highlights: Grouping by ability defines social and academic hierarchies in primary school. Teachers cast an 'invisible hand' peer relations when using ability grouping. Higher ability and majority ethnic children have higher social and academic status. Lower ability and minority ethnic children are marginalised from peers. Ability grouping negatively impacts children's psychosocial wellbeing in school.